Docking Apung pada Kapal MT. Ngagel Dadi - Prasetyo Sofyan; Arika Palapa; Iksan Saifudin; Muhammad Sapril Siregar (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
Maintenance is an activity to prevent damage from an early age that will occur by periodically inspecting equipment using sensors and sophisticated tools. Docking is a process of moving ships from seawater to docking with the help of docking facilities. A shipyard is a place that will later be used to carry out the process of building ships/repairing and maintaining ships. The implementation of ship maintenance on dock requires planned maintenance management by the owner of the ship. In terms of the implementation of maintenance work comes into two: planned and unplanned. An overview of the implementation of docking that occurred on MT ships. NGAGEL SO. As a result, the ship ran aground and ignored the recommended maintenance. The importance of care management carried out must be in accordance with the guidebook. There is support from ship owners to support the maintenance system on the ship. Implement a care management system that complies with maintenance rules. Treatment that is done in accordance with regulations, can help increase the life of the equipment to be used and reduce repair costs and time efficiency.